Employee Scholarship Acceptance By Applying The Mfep Method - Rima Liana Gema; Mutiana Pratiwi; Shary Lusinia; Devia Kartika; Ulya Ilhami Arsyah (Jurnal KomtekInfo, 2020)
The use of computers in people's lives is growing as is the case with companies that provide scholarships for the children of employees who work at the company. The scholarship selection system is still done manually so it is ineffective and inefficient and requires a long time. By using a new system design to assist in data processing of spare part goods, producing a desired system a system is created. In this study the authors used the method of field research, interviews, library research and laboratory research, in conducting analysis using UML (Unified Model Language). The new system will be implemented later to improve the quality of information generated so that these designs can be useful for the company concerned.